CTNI-55. THE CDK4/6 INHIBITOR ABEMACICLIB IN PATIENTS WITH RECURRENT MENINGIOMA AND OTHER PRIMARY CNS TUMORS. (12th November 2021) - Coffee, Elizabeth; Panageas, Katherine; Young, Robert; Morrison, Tara; Daher, Ahmad; Grommes, Christian; Gavrilovic, Igor T; Lin, Andrew; Miller, Alexandra; Schaff, Lauren; Daras, Mariza; DeAngelis, Lisa; et al.
Abstract: BACKGROUND: Medical therapies for recurrent brain tumors are limited. Abemaciclib is a small molecule CDK4/6 inhibitor that has demonstrated antitumor activity in multiple cancer types and crosses the blood-brain barrier. METHODS: We conducted a phase II trial of single-agent abemaciclib in patients with recurrent primary brain tumors utilizing a novel CNS basket trial design with multiple tumor types accrued to separate cohorts including patients with recurrent IDH-wildtype gliomas (Cohort A), any recurrent gliomas requiring cytoreductive surgery (Cohort B), and any other recurrent primary brain tumors (Cohort C) including IDH-mutant gliomas, meningiomas, and other tumor types. In all patients, abemaciclib was administered orally at 200mg twice daily for each 28-day cycle. In cohort B abemaciclib was administered 4-7 days prior to surgery then resumed after recovery. Neuroimaging disease assessments were performed every two cycles. Cohorts were individually assessed for efficacy, tumoral molecular characteristics, and exploratory biomarker analyses. Next generation sequencing was performed on patients who had prior surgery. RESULTS: To date, a total of 61 patients have enrolled and initiated treatment with abemaciclib. Cohort A enrolled 9 patients with IDH-wildtype WHO grade II and III astrocytomas. Cohort B enrolled 10 patients with astrocytomas of varying IDH-status. Cohort C is a diverse group of 42 patients including 22 treatment-refractory meningiomas, 10 IDH-mutant gliomas (5 astrocytomas, 5 oligodendrogliomas), 3 ependymomas, 3 primary CNS lymphomas, 2 pituitary tumors, 1 glioneuronal rosette forming tumor, and 1 diffuse midline glioma. A total of 7 grade 3 toxicities occurred in 6 patients: fatigue (3), neutropenia (2), colitis (1) and seizure (1); no grade 4 toxicities occurred. CONCLUSIONS: We present the results of a novel CNS basket trial looking at the efficacy of abemaciclib across multiple recurrent primary brain tumors. Efficacy results will be presented, highlighting an update on promising results in the 22 patients with recurrent meningiomas.